Management Strategy for Anchovies (Stelephorus Sp) at Batu Belubang Fishing Port, Central Bangka Regency - Wiseli, Retfi; Ferizal, Jemi (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2024)
The Marine and Fisheries Sector plays a very important role in supporting national development as a workforceabsorber, starting from fishing activities, cultivation, processing and distribution to marketing of fishery products.Therefore, the development of the fisheries sector requires special attention from the government in various aspectsfrom upstream to downstream. The abundance of catches of fishermen in Batu Belubang Village is dominated byanchovies. Information from https://babeltoday.com/ dated September 28, 2024 makes it a blessing or a burden forfishermen? To support the process of accelerating fisheries' development from upstream to downstream by utilisingthe potential and availability of raw materials from the catches of Batu Belubang fishermen according to consumerdemand, a study or scientific paper is needed to find a strategy for managing anchovies (Stelephorus Sp) at the BatuBelubang Fishing Port. The research was conducted in Oktober 2024 at the Batu Belubang Fishing Port. ResearchMethods: The data for this research comes from primary data using interview methods with shipowners, fishprocessing business actors in Batu Belubang and the Head of the Batu Belubang Fishing Port. Secondary data fromliterature studies such as: journals, books, the internet and mass media. Analysis of Potential Resources andConstraints Using SWOT. The conclusion of this study is the development of fishery products based on anchovies, theneed for promotion and campaigning for the Movement to Socialise Eating Fish (GEMARIKAN) of Anchovies,training and coaching for anchovy processing with a touch of technology, increasing the length of the Batu BelubangFisheries Port Pier and quota fishing.